2003
DOI: 10.3354/meps247027
|View full text |Cite
|
Sign up to set email alerts
|

Composition and biomass of phytoplankton assemblages in coastal Antarctic waters: a comparison of chemotaxonomic and microscopic analyses

Abstract: We describe the distribution of phytoplanktonic community composition and biomass from the Western Antarctic Peninsula coast (between 64°and 68°S) using 2 analytical techniques: microscopy and HPLC of photosynthetic pigments. Phytoplankton biomass was estimated as chlorophyll a (chl a) by HPLC and chemotaxonomic quantification of microalgae biomass was performed by multiple regression analysis of pigment concentrations. For the estimation of chl a : diagnostic pigment ratios, it was found of primary importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
0
9

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 54 publications
8
67
0
9
Order By: Relevance
“…5, Table 1). The gradients in carbon biomass and chl a concentration were of the same magnitude as others previously reported for this area (Smith et al 1998, Garibotti et al 2003, showing phytoplankton standing stocks several times higher in coastal waters than in open waters (Table 1). Composition of the phytoplanktonic community and diatom populations also changed along the gradient, as indicated by shifts in the dominant algae groups and diatom species in regions differentiated within the area (Fig.…”
Section: Across-shelf Phytoplankton Distribution Patternsupporting
confidence: 72%
See 3 more Smart Citations
“…5, Table 1). The gradients in carbon biomass and chl a concentration were of the same magnitude as others previously reported for this area (Smith et al 1998, Garibotti et al 2003, showing phytoplankton standing stocks several times higher in coastal waters than in open waters (Table 1). Composition of the phytoplanktonic community and diatom populations also changed along the gradient, as indicated by shifts in the dominant algae groups and diatom species in regions differentiated within the area (Fig.…”
Section: Across-shelf Phytoplankton Distribution Patternsupporting
confidence: 72%
“…Phytoplanktonic cell abundance and carbon biomass data were from samples at the 50% PAR depth, presumed to be representative of the UML. This assumption is based on previous studies performed in the area that revealed a uniform vertical distribution of carotenoid pigments (diagnostic of different algae groups), suggesting no major phytoplankton composition variations with depth (Ross et al 2000, Garibotti et al 2003. The 50% PAR depth (5 to 30 m) was always within the UML.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the timing of the development and retreat of sea ice are considered as important factors in the temporal variability of phytoplankton communities in the AP (Arrigo et al, 1999;Garibotti et al, 2003Garibotti et al, , 2005Moline and Prézelin, 1996). Although the dynamics of sea ice are influenced by winds (Stammerjohn et al, 2003, and references therein), here we related these dynamics only with temperature.…”
Section: Interannual Variability In Phytoplankton Temperature and Sementioning
confidence: 99%